Local infiltration analgesia: a 2-year follow-up of patients undergoing total hip arthroplasty - Kuchálik, Ján (J Anesth, 2017)
PURPOSE: Local infiltration analgesia (LIA) is commonly used for postoperative pain management following total hip arthroplasty (THA). However, the long-term effects of the component drugs are unclear. The aim of our study was to investigate functional outcome, quality of life, chronic post-surgical pain, and adverse events in patients within 2 years of undergoing THA. METHODS: The study was a secondary analysis of data from a previous larger study. Eighty patients were randomized to receive either intrathecal morphine (Group ITM) or local infiltration analgesia (Group LIA) for pain management in a double-blind study. The parameters measured were patient-assessed functional outcome [using the Hip dysfunction and Osteo-arthritis Outcome Score (HOOS) questionnaire], health-related quality of life [using the European Quality of Life–5 dimensions (EQ-5D) questionnaire and the 36-Item Short Form Health Survey (SF-36) score], and pain using the numeric rating score (NRS), with persistent post-surgical pain having a NRS of > 3 or a HOOS pain sub-score of > 30. All complications and adverse events were investigated during the first 2 years after primary surgery. RESULTS: Pain intensity and rescue analgesic consumption were similar between the groups after hospital discharge. No differences were found in HOOS or SF-36 score between the groups up to 6 months after surgery. A significant group × time interaction was seen in the EQ 5D form in favor of the LIA group. No between-group difference in persistent post-surgical pain was found at 3 or 6 months, or in adverse events up to 2 years after surgery. CONCLUSION: Analysis of functional outcome, quality of life, and post-discharge surgical pain did not reveal significant differences between patients receiving LIA and those receiving ITM. LIA was found to be a safe technique for THA during the long-term follow-up. However, it should be noted that these conclusions are based on a limited number of patients.